Drugs from Marine Sources - Nuzzo, Genoveffa; Gallo, Carmela (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Thanks to their rich chemodiversity, marine natural products represent a unique source of new bioactive metabolites. As the new leading compounds in drug discovery and development, these molecules may represent challenges for the treatment of a number of human diseases, attracting the attention of many researchers during their chemical and biological studies. This Special Issue covers all fields of drugs research in which marine natural products are involved, including their isolation and characterization, biological activities, and medicinal applications as well as synthetic approaches and their related analogues. The cover picture shows "The Nudibranch mollusk Godiva quadricolor on a sponge, reflected under the surface during the low tide. Fusaro Lagoon, Bacoli (Naples)".